Antioxidant and Anti-tyrosinase Activities of Halymenia durvillei Water Extract Containing R-Phycoerythrin Before and After Microencapsulation - Tiara Silva Khatulistiani; Devi Ambarwaty Oktavia; Ifah Munifah; Endar Marraskuranto (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2023)
Halymenia durvillei water extract (HDWE) contains a dark-pink colored pigment of Rphycoerythrin (R-PE), which its stability is influenced by temperature and pH and possesses biological activities. Microencapsulation could be the solution to preserving the nature of R-PE. This study characterized the HDWE emulsion and analyzed the RPE content, antioxidants, and anti-tyrosinase activities before and after microencapsulation using sodium caseinate and maltodextrin (M-HDWE). Halymenia durvillei was extracted in distilled water (ratio 1:2, w/v) for 24 hours at 4 °C. Sodium caseinate to maltodextrin coating ratios were 1:2; 1:4; 1:6 and 1:12. Emulsion (viscosity, color, and R-PE content) and powder characteristics (surface morphology) were determined using Brookfield DV2T, ColorFlex EZ Hunterlab, UV-VIS spectrophotometry, and JeolSEM, respectively. The antioxidant and anti-tyrosinase activities were determined using the Ferric Reducing Antioxidant Power (FRAP) and mushroom tyrosinase assays. The Commision Internationale d’Éclairage (CIE) L* a* b* colorimetry result showed that the more maltodextrin and the lower viscosity, the more intense the emulsion color. Despite HDWE having roughly six-fold more R-PE content, all M-HDWE treatment samples exhibited equal R-PE contents (p 0.05). The M-HDWE 1:2; 1:4; 1:6; and 1:12 microcapsules had more wrinkled spheres and fewer cracks than MHDWE 0. The M-HDWE 1:2 had 33.10% lower antioxidant activity than the HDWE and was the highest compared to other M-HDWE compositions (17.15±1.27 µM/µg extract, p 0.05). Meanwhile, all M-HDWE had low anti-tyrosinase activity. It can be concluded that microencapsulation could be a solution for preserving HDWE’s antioxidant activity but not its anti-tyrosinase activity